Chronic obstructive pulmonary disease across three decades: trends, inequalities, and projections from the Global Burden of Disease Study 2021 - Wang, Yan; Han, Ruiyang; Ding, Xiao; Feng, Wenjia; Gao, Runguo; Ma, Anning (Frontiers in Medicine, 2025)
ObjectiveTo assess the global burden of chronic obstructive pulmonary disease (COPD) and cross-country inequalities from 1990 to 2021 and project changes until 2045.MethodsData on prevalence, mortality, and disability-adjusted life-years (DALYs) for COPD were extracted from the Global Burden of Disease Study 2021 (https://vizhub.healthdata.org/gbd-results/). Trends were analyzed globally, regionally, and nationally, considering population growth, aging, and epidemiological changes. Inequalities were quantified using the World Health Organization’s health equity framework. Future projections were estimated to 2045.ResultsFrom 1990 to 2021, global age-standardized rates of COPD prevalence, mortality, and DALYs declined annually by −0.04, −1.75%, and −1.71%, respectively. However, absolute cases, deaths, and DALYs increased by 112.23, 49.06, and 40.23%, driven by population growth and aging. Men consistently showed higher age-standardized rates. East Asia reported the highest absolute cases and deaths, while South Asia had the largest DALYs. High-income North America and Oceania had the highest age-standardized rates, while Australasia and Eastern Europe saw the steepest declines in prevalence and mortality, respectively. Disparities in COPD burden across sociodemographic index levels widened over time. By 2045, absolute numbers of COPD cases, deaths, and DALYs are projected to rise despite declining age-standardized rates.ConclusionWhile global age-standardized rates of COPD prevalence, mortality, and DALYs have declined, the absolute burden has increased due to demographic shifts. Persistent disparities in COPD burden, particularly in low- and middle-sociodemographic index regions, underscore the need for targeted prevention and management strategies.